When we go camping - Ruurs, Margriet; Kiss, Andrew (Toronto : Tundra Books ; Plattsburgh, N.Y. : Tundra Books of Northern New York, 2004)
Two children have fun camping in the wilderness.
Booklist
Resource Links
School Library Journal
3.0
K-3.
K-3
Keywords: Camping -- Juvenile fiction; Camping -- Fiction; Camping -- Fiction